Assessment of Mangroves in Guang-guang, Dahican, Mati City, Davao Oriental - Marvelou Yap; Maria Noe-Mae Fe Yap; John Glen Seniel (Davao Research Journal)
This study aims to identify mangrove species in Guang-guang, Dahican, Mati, and Davao Oriental. Guang-guang served as the sampling site of the study. Three stations were established in each forest type or zone. The presence or absence of a particular mangrove species within a 100m2 plot and their identification code were recorded. Plots were randomly established in each forest type or zone. Mature mangroves (DBH > 4 cm) found in each plot were counted and measured for diameter at breast height 1.5m. If the density of saplings (< 4cm DBH and height > 1m) was high and uniform, a 5m x 5m plot was established inside the 10m x 10m plot, and the saplings were counted. The density of seedlings (height < 1m) was high and uniform. A 1m x 1m subplot was established for actual counts. There were nine mangrove species, identified these were Ceriops tagal, Rhizophora stylosa, Rhizophora apiculata, Bruguiera gymnorhiza, Sonneratia alba, Avicennia officinalis, Pemphis acidula, Aegiceras corniculatum, and Avicennia alba. These were common mangrove species found in the study area.